Effectiveness of Awareness Programme on Criteria of NABH &Its Implementation among Health Care Workers at a Tertiary Care Hospital - H.N. , Ravindra; D. Patel, Prachi; M. Patel, Purvi; J. Patel, Rashmi; N. Sodha, Hanish (International Journal of Psychosocial Rehabilitation, 2020)
Background of the study: Health care system of India currently operating within an environment of rapid social, economic, technological, and Hospitals are an integral part of the health care system Declaration of Human Rights was generated lately because of increasing awareness among the consumer market for such things as medical tourism insurance and the corporate sector, which have accelerated the demand for quality in health care services. That is, the paternalistic model of informative or physician-centered care is shifting to patient-centered health care quality improvement movement began in the early 1900s with the assessment of hospital condition establishment of standards and services. NABH is a constituent board of the Quality Council of India, set up to establish and operate an accreditation program for healthcare organizations. The board is structured to cater to the much-desired needs of the consumers and to set benchmarks for the progress of the health industry. Board, while being supported by all stakeholders, including industry, consumers, and government, has full functional autonomy in its operation. Aims and Objectives: The investigator aimed to find the effectiveness of the awareness program regarding NABH criteria among healthcare workers. Material and Methods: One group pre-test, post-test research design, which belongs to pre-experimental design, was selected to assess the effectiveness & awareness program regarding criteria of NABH among the 287 health care workers working at a tertiary hospital in Vadodara. Simple random sampling was used to select the samples. Results: The collection of the data was tabulated and analyzed by using descriptive and inferential statistics. The pre-test mean score was 11.85, and the post-test mean score was 22.67. The post-test level of knowledge score is significantly greater than the pre-test knowledge mean score. The t value of 34.24 is more than the tabulated value at the 0.05 level of significance. Conclusion: According to the calculation of both pre-test and post-test score study reveals that there was improvement in the knowledge of health care workers after administering the awareness program NABH. Hence it indicates that the awareness program was effective.